Wacana Negara Islam: Kajian Kritis Kontruksi Pemikiran Khilafah Ala Hizbut Tahrir - Eko Nani Fitriono; Suhono Suhono (Ri'ayah: Jurnal Sosial dan Keagamaan, 2017)
This paper aims to synergize the discourse about the state and Islam in two views of thought, namely Hizb ut-Tahrir thinking with the concept of the concept of the state of the concept of Khilafah al-Islamiyah which is bound to the labelitas and nostalgia longing for a system that was built in the time of the Prophet until the Ottomans ( 1924 AD) dealing with the thought of non-Hizbi scholars who are not bound by religious symbolization that adheres to the values of the sub-khilafah al-Islamiyah that can be accomplished systemically through any system of origin of the value of substance on the forms in accordance with Islamic values, not putting symbolic value as a goal, but attempting to build a system substantially that does not conflict with Islam itself. Data collection method of this research is through the documentation of a number of books by Sheikh Taqiyuddin an-Nabhani as the foundation layers of Khilafah thought that according to him as the only way for Muslims to regain their power from the colonization of the system of infidels. However the efforts of an-Nabhani can be said as a new thought that must face to face with other ideology and thought, for that will be very worth to be criticized. First, the khilafah system is regarded as something irrelevant to the current situation and condition, in which the Muslim life is already scattered throughout the world. Secondly, according to the jumhur ulama there is no obligation to appoint a single leader like khalifah / imamah when Muslims are unable to do so, even according to Imam al-Haramain al-Juwaini Muslims can appoint leaders in their respective regions. Thirdly, Muslims should not be caught up in the symbols and formality of names that seem Islamic, but must commit to the substance of things. In the popular adage among the scholars it issaid:مظهز ال جىهزالب ال بزةب ع ال"The substance of the substance is the substance, not the symbol or outward appearance" or in another phraseسم اإل الب سمى م ال بزةب ع ال"The subject of the subject is something that is named, not the name "Thus, fighting for the establishment of values substantively with regard to Islamic teachings in a State is far more important than fighting for the establishment of the symbols of an Islamic state.